The Misery of Victory: France’s Struggle for the Versailles Treaty - Marks, Sally (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractFrom 1920 to this day, French policy after Versailles has been termed unreasonable, but was it really? Britain and the United States thought so, and effectively deemed it simplest if France would accept defeat in the aftermath of deliverance. They mistakenly thought Germany wanted to forget the past, as they did, and they misread the power balance, exaggerating Germany's temporary prostration and France's fleeting ascendancy. Thus they feared French predominance.France worried about survival. She acted consistently to prevent a return of German predominance. France was realistic about the facts, if not always about her erstwhile allies. She was sometimes tactless and often disorganized; she clearly had failures of courage, will, propaganda, and economic insights. She knew, however, that she had not won the war and could not impose the peace alone against a largely intact Germany whose power position had been enhanced by the fragmentation of Europe. She saw that small-power alliances could not compensate for the Russian tie, that Germany was stronger, and that treaty clauses to offset that fact were mostly temporary. Thus France relied on Britain and the United States for security because without them she was lost, refusing to face mounting evidence that they were at best neutral, at worst in Germany's camp.Germany and France both concentrated on Britain in their efforts respectively to undo or preserve the Versailles treaty. Germany had the easier task, as Britain soon wanted to circumvent the treaty too. Preoccupied with imperial and economic problems, Britain feared German market competition to finance reparations and also France's dwindling military power; she was hostile to her historic foe and eager to be the fulcrum of the power balance again. Hence, seconded substantially by the United States, she tried to strengthen Germany at French expense ― a state of affairs which largely explains why France painfully progressed in five years from a determination to enforce key treaty clauses to defeated resignation.The chief battlegrounds of “the continuation of war by other means” were reparations and disarmament. The Ruhr conflict was the climax of the first battle, and the Dawes Plan embodied France's defeat. Locarno signalled both abandonment of requiring Germany's disarmament and her return to equality and diplomatic respectability. Thereafter a defeated France built the Maginot Line, tried with scant success to salvage something in the Young Plan, and clutched at straws, as in Briand's attempt to freeze the political status quo in his “European Union” scheme.France's failure stemmed partly from her own errors but primarily from Anglo-American defection. As admitting defeat or combining with Soviet Russia were politically unthinkable, she struggled on in vain, trying not to face facts. Yet her decision at the outset to accept a misnamed and fatefully moderate Armistice may have contributed to her eclipse, leaving France only the misery, not the grandeur, of victory.